The score [videorecording (DVD)] - Smyth, Malachi; Poulter, Will; Flynn, Johnny; Flynn, Johnny; Wilson, Lydia, 1984-; Ackie, Naomi (Gravitas Ventures, 2022)
Boldly combines real time heist-thriller suspense with offbeat romance and a killer soundtrack, starring and featuring the music of Johnny Flynn, alongside Naomi Ackie and Will Poulter.